Are long shifts, overtime and staffing levels associated with nurses' opportunity for educational activities, communication and continuity of care assignments? A cross-sectional study - Talia Emmanuel; Chiara Dall'Ora; Sean Ewings; Peter Griffiths (Elsevier, 2020)
Background & Objectives: Previous research demonstrates the impact of workforce organisation variables on quality of care and nurse wellbeing. However, the extent to which these variables influence completion of important "ancillary" nursing work is unexplored. This type of work can include discussion of care information between colleagues, promoting continuity of care during shift changes, and participating in continuing professional development programs. Although ancillary work is not usually classified as direct nursing care, it remains critical to the delivery of safe and effective care, as well as for building nurse resiliency and workforce capacity. Our aim was to examine the relationship between ≥12-hour shifts, overtime, and lower staffing levels and opportunities for completing ancillary work. Design & Methods: Cross-sectional survey of 2990 registered nurses in 48 hospitals in England. Relationships were estimated through generalised linear mixed models. Results: When compared to ≤8 hour shifts, nurses working ≥12-hour shifts were less likely to report having staff education programs (OR=0.58, 95% CI [0.43, 0.76]) and enough opportunity to discuss patient care with other nurses (OR=0.72, 95% CI [0.56, 0.92]). When compared to working overtime, nurses working only scheduled hours reported more opportunities these activities (OR=1.31, 95% CI [1.07, 1.61] and OR=2.06, 95% CI [1.72, 2.47] respectively), and reported fewer cases of losing care information during handovers (OR=0.72, 95% CI [0.60, 0.86]). Furthermore, with each additional patient per nurse (i.e., higher workloads), poorer outcomes for all variables of interest were observed. Conclusion: Long shifts, overtime, and lower staffing levels are associated with fewer reported opportunities for completing ancillary work. Our findings contribute to the large body of literature exploring the drawbacks of implementing short-term solutions for nurse shortages and warrant careful consideration when establishing nursing shift rotas and staffing policies.